IMPLEMENTATION OF LOW NOISE AMPLIFIER ON ANTENNA FOR PARTIAL DISCHARGE MEASUREMENT - P. Sihite, Lasro
In the electric industry environment, high-voltage equipment plays a vital role in ensuring reliable and secure energy delivery. Equipment such as generators, transformers, insulators, and high-voltage conductors require effective insulation to maintain optimal performance. Insulation serves to separate high-voltage components from those at lower voltage levels, preventing electrical leakage that could lead to serious equipment damage or even fires. Adequate insulation condition is key to maintaining the operational integrity of high-voltage equipment. However, insulation failures can occur due to several factors. Natural aging of equipment, high loads, and harsh environments are some of the factors that can contribute to insulation quality degradation. In high-voltage equipment, insulation can take the form of solid materials, gases, or liquids, all of which may degrade due to the presence of strong electric fields, resulting in gradual insulation breakdown. This study proposes a novel approach to detecting potential insulation failures by utilizing ultra-high-frequency (UHF) antenna technology and low-noise amplifiers (LNA). The Low Noise Amplifier (LNA) is a device that amplifies signals received from the antenna while reducing noise that could affect detection accuracy. The research aims to enhance the sensitivity of insulation failure detection by integrating LNAs with UHF antennas. Research findings indicate that the use of LNAs with antennas successfully enhances the detection of disruptive signals in insulation. A comparison between power reception measurements (PD) using antennas without LNAs, antennas with LNAs, and other measurement methods such as High Frequency Current Transformer (HFCT) demonstrates a significant increase in disruptive signal detection in insulation. The utilization of UHF antennas with LNAs proves to be an effective solution for detecting potential insulation damage with greater accuracy, thereby aiding in preventing more severe damage to both equipment and the overall electrical infrastructure.